A promoção do desenvolvimento nacional sustentável por meio das licitações e contratos administrativos - Lima, Luciana Lara Sena (2015)
This work has as object of study discuss about the promotion of sustainable national development through administrative procurement and contracting carried out by the Brazilian Government. For this, it has to, at first, a historical analysis (international and national), the concept and dimensions of sustainability. Then, far-there will be an approach to the main aspects of bids and administrative contracts in the Brazilian legal system, having as basis the article 37, item XXI of the Federal Constitution of 1988 and Law n°. 8.666 - 93. Finally, it will be specifically analyzed the bids and sustainable hires through internal regulatory instruments, namely, the National Environmental Policy (Law n°. 6.938 - 1981), the National Policy on Climate Change (Law n°. 12.187 - 2009 ), Normative Instruction n°. 1 of 2010 - Ministry of Planning, Budget and Management, the National Policy on Solid Waste (Law n°. 12.305 - 2010), Differentiated Contracting Regime (Law n°. 12.462 - 2011), Decree Presidential 7746, 2012, among others, and also point out some practical examples of measures taken to better understanding and comprehension of the subject defended.